The autoimmune diseases - Rose, Noel R.; Mackay, Ian R. (Elsevier Academic Press, 2006)
Since publication of the Third Edition in 1998, the understanding of the immune mechanisms underlying autoimmunity and autoimmune disease has significantly deepened and broadened. This Fourth Edition incorporates new material and combines common themes underlying inductive and effector mechanisms and therapies that relate generally to the autoimmune disorders. It discusses the biological basis of disease at genetic, molecular, cellular, and epidemiologic levels. New to This Edition: * Tissue-specific interventions to arrest or "cure" autoimmune disease * Bone marrow eradication and replacement * Both basic science and clinical medicine is covered * Boxed points to emphasize key features of each chapter